2021
DOI: 10.1155/2021/5972962
|View full text |Cite|
|
Sign up to set email alerts
|

Automated Diagnosis and Localization of Melanoma from Skin Histopathology Slides Using Deep Learning: A Multicenter Study

Abstract: In traditional hospital systems, diagnosis and localization of melanoma are the critical challenges for pathological analysis, treatment instructions, and prognosis evaluation particularly in skin diseases. In literature, various studies have been reported to address these issues; however, a prominent smart diagnosis system is needed to be developed for the smart healthcare system. In this study, a deep learning-enabled diagnostic system is proposed and implemented that it has the capacity to automatically det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…In this regard, a higher number of patient samples is commonly preferred over a large number of images. The number of patients included for training, validation and testing in the current investigation is within the reported range of previous studies ( 9 , 11 , 26 ). Currently, there is no consensus on the minimum number of cases that should be included in a deep learning study.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In this regard, a higher number of patient samples is commonly preferred over a large number of images. The number of patients included for training, validation and testing in the current investigation is within the reported range of previous studies ( 9 , 11 , 26 ). Currently, there is no consensus on the minimum number of cases that should be included in a deep learning study.…”
Section: Discussionmentioning
confidence: 59%
“…In skin diseases, the technique has been mainly used in neoplastic diseases so far. While most reports focus on either melanocytic ( 9 11 , 30 ) or non-melanocytic ( 26 ) lesions, data on both melanocytic and non-melanocytic lesions, non-tumor skin lesions or anatomical tissue structures are scarce ( 12 , 26 ). Although there are honorable exceptions ( 31 ), most of the published studies on deep learning on histopathological slides do not make their annotated data, the full dataset of image patches and/or their code available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al. proposed a deep learning-based pathology diagnosis system for melanoma whole slide imaging (WSI) classification and generated a multicenter WSI database for model training, which could assist the pathological diagnosis of melanoma diseases ( 11 ). Xie et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas et al found that some of the most common skin cancer diagnoses, such as basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and intraepidermal carcinoma (IEC) are amenable to deep learning methods (10). Li et al proposed a deep learning-based pathology diagnosis system for melanoma whole slide imaging (WSI) classification and generated a multicenter WSI database for model training, which could assist the pathological diagnosis of melanoma diseases (11). Xie et al collected 2,241 digital whole-slide images from 1,321 patients and constructed a multicenter dataset for training both ResNet50 and Vgg19 to test performance with the classification of melanoma and nevi.…”
Section: Introductionmentioning
confidence: 99%